Quality of siltstones for concrete aggregate from Nallu Khola area, Kathmandu valley - Maharjan, Dev Krishna; Tamrakar, Naresh Kazi (Journal of Nepal Geological Society, 2004)
The siltstones of the Tistung Formation are the major source of concrete aggregate in the Kathmandu valley. A member of quarries are operating in the valley, especially in the vicinity of the Nallu Khola, for more than three decades. Randomly collected siltstone samples from both banks of the Nallu Khola were studied to reveal their petrography and chemical composition. Crushed rock fragments were investigated to determine their overall aggregate properties. Tests were carried out to determine shape, flakiness index, elongation index, degree of induration, Schmidt hammer value, dry density, water absorption value, aggregate crushing value, and aggregate impact value. The test results indicate that the aggregates are physically, mechanically, and chemically sound.